1998
DOI: 10.1029/98rg01691
|View full text |Cite
|
Sign up to set email alerts
|

Thermal plasma and neutral gas in Saturn's magnetosphere

Abstract: Abstract. Saturn's magnetosphere contains plasma and neutral particles from Saturn's atmosphere, the rings, the inner icy satellites, and Titan. This paper reviews the observations of plasma and neutrals near Saturn. Plasma conditions were observed during the Pioneer 11 and Voyager 1 and 2 flybys of Saturn. Neutral H was observed by the Voyagers; neutral OH has been observed by the Hubble Space Telescope. The attempts which have been made to understand the physical processes behind the data are also discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 55 publications
10
121
0
1
Order By: Relevance
“…The most obvious source of OH is dissociation of sputtered H 2 O molecules from satellites' surfaces and Saturn's rings (e.g., Johnson et al 1983;Pospieszalska & Johnson 1989;Shi et al 1995). The model of Richardson (1998) demonstrated that the required source strength of OH radicals is at least an order of magnitude larger than can be supplied by sputtering. Jurac et al (2001) found that the missing water source is even a more severe problem than concluded by Richardson (1998).…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious source of OH is dissociation of sputtered H 2 O molecules from satellites' surfaces and Saturn's rings (e.g., Johnson et al 1983;Pospieszalska & Johnson 1989;Shi et al 1995). The model of Richardson (1998) demonstrated that the required source strength of OH radicals is at least an order of magnitude larger than can be supplied by sputtering. Jurac et al (2001) found that the missing water source is even a more severe problem than concluded by Richardson (1998).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field strength in this region is $320 nT, and the electron density is $60/cm 3 [Richardson, 1998]. The background ions and electrons have temperatures of $50 and 5 eV, respectively [Sittler et al, 1983;Saur and Strobel, 2005].…”
Section: Interaction Of Enceladus With the Saturnian Plasmamentioning
confidence: 99%
“…The equatorial proton to water group density ratio was adjusted to give the b value that gave the best agreement (b = 3) with the results of Richardson [1998], as discussed in the previous section. The magnetic mirror force was included in the iteration procedure, but was initially assumed to be zero, i.e., P k = P ?…”
Section: à3mentioning
confidence: 99%
“…It then follows from the equation for the scale height (given earlier) that b = 4(T H +/T W +) 1/2 . The best currently available measurements of the ratio of the temperature of the protons to the temperature of the water group ions are from Richardson [1998]. temperatures given by Richardson [1998] is for b = 3, which corresponds to a ratio of the proton temperature to the water group ion temperature of T H +/T W + = 0.5.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation